Transformation of Islamic Religious Education Learning in the Digital Era: Learning Modalities and Educational Challenges in the 21st Century - Dwi Jati Marta; Uthman Shehu Lawal (Indonesian Journal of Islamic Educational Review, 2026)
This research analyzes the transformation of Islamic Religious Education learning in the digital era by specifically examining its alignment with students’ learning modalities and the demands of 21st-century education. The originality of this research lies in its integrative analytical framework, which synthesizes digital learning transformation, Visual-Auditory-Kinesthetic (VAK) learning modalities, and 21st-century competencies within the context of Islamic education an intersection that remains underexplored in existing literature. Employing a qualitative literature review approach, this research systematically analyzes books and peer-reviewed journal articles published within the last five years. Data were examined through thematic categorization and theoretical triangulation to ensure analytical rigor and credibility. The findings reveal that digitalization significantly enhances Islamic Religious Education learning using visual and audiovisual media, flexible digital platforms, and learner-centered instructional strategies that support learning autonomy and engagement. However, the research also identifies persistent challenges, particularly teachers’ limited capacity to design pedagogically sound, creative, and contextually relevant digital teaching materials. These findings indicate that technological integration alone is insufficient without concurrent development of teachers’ pedagogical and digital competencies grounded in Qur’anic and Prophetic values. This research concludes that the digital transformation of Islamic Religious Education is effective when technology is integrated with adaptive pedagogy and learning modalities responsive to students’ characteristics. Practically, the findings highlight the need for systematic teacher training in digital instructional design, while theoretically, this research contributes to the discourse on Islamic education by positioning digital pedagogy as a value-oriented, not merely technical, innovation.